การมีส่วนร่วมของประชาชนในการวิเคราะห์ผลกระทบสิ่งแวดล้อมและสุขภาพ กรณีศึกษา โครงการขยายกำลังการผลิตโรงไฟฟ้ากระบี่ / A Public Participation in Environmental Health Impact Assessment: A Case Study of Krabi Power Plant Expansion Project - / Manida Fuangchoonuch and Chutarat Chompunth, มานิดา เฟื่องชูนุช และจุฑารัตน์ ชมพันธุ์ (Journal of Community Development Research (Humanities and Social Sciences), 2017)
ปัจจุบันปัญหาความขัดแย้งจากโครงการพัฒนาขนาดใหญ่ที่ส่งผลกระทบต่อสิ่งแวดล้อมและสุขภาพอย่างรุนแรงทวีความรุนแรงมากขึ้น เนื่องจากขาดการมีส่วนร่วมของประชาชนอย่างแท้จริง งานวิจัยนี้จึงมีวัตถุประสงค์เพื่อศึกษากระบวนการมีส่วนร่วม ปัจจัยความสำเร็จ ปัญหาและอุปสรรค เพื่อนำไปสู่การนำเสนอแนวทางในการส่งเสริมและสนับสนุนการมีส่วนร่วมของประชาชนในการวิเคราะห์ผลกระทบสิ่งแวดล้อมและสุขภาพ โดยใช้แบบสัมภาษณ์แบบเชิงลึกเป็นเครื่องมือในการเก็บรวบรวมข้อมูลจากกลุ่มตัวอย่างผู้มีส่วนได้ส่วนเสีย ร่วมกับการศึกษาเอกสารที่เกี่ยวข้อง ผลการศึกษากระบวนการมีส่วนร่วมของประชาชนตามกรอบการประเมิน พบว่า พื้นที่โครงการอยู่ใกล้กับพื้นที่ชุ่มน้ำปากแม่น้ำกระบี่ที่มีความสำคัญระดับนานาชาติ เป็นแหล่งเศรษฐกิจและศูนย์กลางความหลากหลายชีวภาพทางทะเล ในส่วนของกฎหมายมีช่องว่างในทางปฏิบัติทำให้กระบวนการมีส่วนร่วมดังกล่าวยังไม่สามารถบรรลุเจตนารมณ์ที่แท้จริง และแผนพัฒนากำลังการผลิตไฟฟ้าของประเทศไทยมิได้พิจารณาถึงศักยภาพด้านพลังงานที่มีอยู่ รวมถึงความต้องการของคนในพื้นที่อย่างแท้จริง นอกจากนี้ประชาชนยังมีอุปสรรคในด้านการได้รับข้อมูล ซึ่งอาจยังไม่เพียงพอต่อกระบวนการตัดสินใจ เนื่องจากข้อมูลที่โครงการนำเสนอแก่ประชาชนเป็นข้อมูลด้านเดียวและยังไม่ชัดเจนเพียงพอ ทำให้ประชาชนเกิดความสับสน ในส่วนของรายงานการวิเคราะห์ผลกระทบต่อสิ่งแวดล้อมและสุขภาพ พบว่า ระบบฐานข้อมูลด้านสุขภาพของประเทศยังไม่สามารถวิเคราะห์เชื่อมโยงผลกระทบด้านสิ่งแวดล้อมกับผลกระทบด้านสุขภาพจากการดำเนินโครงการฯ ได้ นำไปสู่ความไม่ชัดเจนของมาตรการลดผลกระทบต่อสุขภาพ ด้านความขัดแย้งในพื้นที่เป็นผลมาจากการได้รับผลประโยชน์ที่แตกต่างกันของคนสองกลุ่ม ในส่วนของปัจจัยความสำเร็จของกระบวนการมีส่วนร่วมฯ ต้องอาศัยปัจจัยด้านเทคนิค ปัจจัยด้านบุคคล และปัจจัยด้านกระบวนการประกอบกัน อย่างไรก็ตาม การดำเนินกระบวนการมีส่วนร่วมฯ ของโครงการพบปัญหาและอุปสรรคที่เกิดจากข้อจำกัดด้านกฎหมาย ข้อจำกัดจากเจ้าของโครงการ และข้อจำกัดที่เกิดจากประชาชนในพื้นที่ ทั้งนี้ แนวทางในการพัฒนากระบวนการมีส่วนร่วมฯ ของโครงการให้ประสบความสำเร็จ ภาครัฐควรพิจารณาปรับปรุงกฎหมายให้ทันสมัยและกำหนดบทลงโทษของกฎหมายที่เกี่ยวข้องให้ชัดเจน พัฒนาระบบฐานข้อมูลด้านสุขภาพ มีความโปร่งใสในการดำเนินงาน รับฟังความคิดเห็นของประชาชนตั้งแต่เริ่มกระบวนการ เพื่อให้ทราบความต้องการที่แท้จริงของประชาชนในพื้นที่ เสริมขีดความสามารถของชุมชนในด้านวิชาการ ในส่วนของภาคประชาชนนั้นควรเปิดใจรับข้อมูลทั้งด้านบวกและด้านลบของโครงการอย่างไม่มีอคติ      There have been increasing conflicts regarding large developmental projects that have severe impacts on the environment and the people’s health. Such conflicts arise from lack of genuine public participation. This research aims to study the participation process of the Krabi Power Plant Expansion Project, success factors, problems, and obstacles, and to propose ways to encourage and support public participation in assessing the project’s environmental and health impacts. In order to investigate the aforementioned process, the application of the CIPP-I model was employed, along with in-depth interviews with samples of stakeholders and the study of related documents. The results of the evaluation of the public participation in the project revealed that the project was located in the wetlands of the Krabi estuary, which has international stature in terms of economy and marine biodiversity. Despite the existing laws, legal practice loopholes have prevented the true success of public participation. Thailand’s development plan for increasing the country’s power generation does not take into account its existing energy potentials and the needs of local people. The obstacles also include the information provided to the people, which may be inadequate for their ability to make decisions; the information is offered solely by the project and without clarity, causing public confusion. The analysis of the environmental and health impacts indicated a problem with the health database, preventing the feasibility of a clear analysis of the relationship between the environmental and health impacts during the project’s execution, which leads to unclear measures for decreasing health impacts. In addition, conflicts in the area result from contrasting profits for two groups of people. Success factors of the public participation relies on technical, personal and processes factors. However, the problems of the process implementation caused by the limitations of the law, project owner and people in the area. The methods for enabling the success of public’s participation in the environmental and health impact assessment of the project are proposed as follows: modification of national laws appropriate for modern society and the stipulation of clear legal punishment related to the issue; improvement of health databases; transparency regarding the project’s execution; welcoming of public participation from the beginning of the project so that the genuine needs of the local people can be heard; and the educational empowerment of the people. It is also suggested that the people should be open-minded and objectively welcome information regarding both the advantages and disadvantages of the project.
Keywords: การมีส่วนร่วมของประชาชน การวิเคราะห์ผลกระทบสิ่งแวดล้อมและสุขภาพ โรงไฟฟ้าถ่านหิน ความขัดแย้ง; Public Participation, Environmental Health Impact Assessment, Coal-Fired Power Plant, Conflict